Noise Induced Hearing Loss among Aircrews of Bangladesh Air Force - Islam, Iftekharul; Jobair, Md Abdullah Al; Ahsan, Mohammad Ahmed; Ahmad, Mushtaq; Hossain, Mohammad Delwar; Wahab, Md Abdu (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Noise-induced hearing loss is a significant, often unrecognized health problem among the military pilots. Advanced aircraft are powerful and more efficient but generate high noise causing noise-induced hearing loss (NIHL) among military pilots. Aim: To determine the prevalence of noise-induced hearing loss among pilots of the Bangladesh Air Force (BAF) and its association with aircraft type and flying hours. Methods: This cross-sectional study was carried out at Central Medical Board (CMB), Bangladesh Air Force (BAF) Dhaka from April 2017 to March 2018. The audiometry was done in the ENT department of CMB, BAF. Pure-tone audiometry was used to measure hearing thresholds and following pure tone frequencies were used for the test: 0.25, 0.5, 1, 2, 3, 4, 6 and 8 kHz. The association between flight hours and the development of noise-induced hearing loss was analyzed in the different age groups. Results: The study revealed NIHL in the aircrew was 16.5% with a higher prevalence among the helicopter pilots (18.6%) as compared with fighter (16.7%) and transport (11.5%) pilots. The left ear was affected in most of the cases than the right ear. Pilots of more than 40 years old and ≥1500 flying hours had a significantly higher hearing threshold compared with other categories. Conclusion: Exposure to noise in aircrew is unavoidable. By avoiding prolonged exposure to loud noise environments and utilization of personal hearing safety devices can prevent noise-induced hearing loss. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 12-15